ANALYSIS OF SOIL ORGANIC CARBON CONTENT, TOTAL SOIL NITROGEN, AVAILABLE SOIL PHOSPHORUS, AND SOIL DENSITY IN INCEPTISOL SOILS UNDER VARIOUS GROUND COVER CROPS VEGETATION - Erwin Junaidi Lubis; Rhiki Budianto (Jurnal Media Akademik (JMA), 2026)
Loamy soil is one of the characteristics of fertile soil, but basically loamy soil is not necessarily considered healthy soil. Soil fertility is determined by the dynamics of organic matter and the availability of essential macro nutrients contained in the soil. Loamy soil currently influences the decomposition process of organic matter in the soil. Inceptisol soil is a young soil type that continues to develop and has low to moderate organic matter content depending on the vegetation that occurs on the soil. In managing the fertility and health of Inceptisol soil, improvements are made by adding organic matter and understanding the dynamics of nutrients contained in Inceptisol soil. Soil fertility is a very important aspect in agriculture to support plant growth.